“PARTICIPANTS OF THE SECOND WORLD WAR FRONTS ARE ETERNALLY ALIVE IN OUR HEARTS.” (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article examines the participation of the people of Uzbekistan in the Second World War and its human consequences through the example of the Djulliyev family—our own family. In particular, the military paths of my grandfathers Hasan, Husan, and Shamsiddin Djulliyev at the front, the emotional experiences of their mother, my grandmother Maryam, as she sent her sons off to war, the long years of painful waiting endured by my grandfather Sobir, and the devoted labor of women who remained on the home front are analyzed on the basis of historical documents and oral memories. The article aims to show that the war was not only a military conflict, but also a profound human tragedy.